2024
DOI: 10.1021/acs.jafc.3c08900
|View full text |Cite
|
Sign up to set email alerts
|

Egg Yolk Selenopeptides: Preparation, Characterization, and Immunomodulatory Activity

Qian Zhao,
David Julian McClements,
Junhua Li
et al.

Abstract: In this study, egg yolk selenium peptides (Se-EYP) were prepared using double-enzyme hydrolysis combined with a shearing pretreatment. The properties of the selenopeptides formed were then characterized, including their yield, composition, molecular weight distribution, antioxidant activity, in vitro digestion, and immunomodulatory activity. The peptide yield obtained after enzymatic hydrolysis using a combination of alkaline protease and neutral protease was 74.5%, of which 82.6% had a molecular weight <1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…R. Ling et al [ 14 ] prepared Se-enriched peptides by enzymatic hydrolysis of CV proteins using Alcalase and Dispase, and found that Se-enriched peptides increased mRNA expression of GPX1 and NGFR in ethanol-treated L-02 hepatocytes, confirming their protective effect against ethanol-induced liver injury. Q. Zhao et al [ 15 ] prepared egg yolk Se-enriched peptides using Alcalase and Dispase hydrolysis combined with shear pretreatment, which exhibited excellent immunoassays, including immune organ index, serum levels of immune factors, splenic histopathological changes, and hepatic Se content. Notably, the synergistic effect of Se and peptides not only promotes Se absorption in the human body [ 16 ], but also enhances the biological activity of the peptides themselves [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…R. Ling et al [ 14 ] prepared Se-enriched peptides by enzymatic hydrolysis of CV proteins using Alcalase and Dispase, and found that Se-enriched peptides increased mRNA expression of GPX1 and NGFR in ethanol-treated L-02 hepatocytes, confirming their protective effect against ethanol-induced liver injury. Q. Zhao et al [ 15 ] prepared egg yolk Se-enriched peptides using Alcalase and Dispase hydrolysis combined with shear pretreatment, which exhibited excellent immunoassays, including immune organ index, serum levels of immune factors, splenic histopathological changes, and hepatic Se content. Notably, the synergistic effect of Se and peptides not only promotes Se absorption in the human body [ 16 ], but also enhances the biological activity of the peptides themselves [ 17 ].…”
Section: Introductionmentioning
confidence: 99%